Mediatization of Library on Instagram as a Promotional Medium - Fitri Handayani; Rhea Rowena U. Apolinario (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2023)
Background of the study: In addition to being a medium of communication, social media is also used for promotion media for institutions that can cause dramatization processes. Mediatization at the Library aims to understand the role of social media such as Instagram as a promotional activity in the Library of Dispusip Kota Sungai Penuh. Purpose: The purpose of this study is to explain the mediatization of libraries through Instagram social media. Libraries use social media as a promotional medium to reach users during the pandemic. Method: This research is a study using a qualitative approach. The collection technique is carried out by observing directly the Instagram account owned by each library of Dispusip Kota Sungai Penuh. Findings: Dispusip Kota Sungai Penuh uses Instagram library to promote library collections, promote library activities and services, upload photos or photos of library activities, develop distribution services, especially book lending, activities within the library, etc. Instagram is a new method for the Library of Dispusip Kota Sungai Penuh Library in order to attract visitors or public leaders, especially the millennial generation. The change in the form of promotional media toward digital media can be in the form of information in visual and audiovisual form. Conclusion: The existence of Instagram affects the pattern of promotional behavior of the Dispusip Kota Sungai Penuh Library because it has been mediated by technology.